A letter by the Regional Editor for Oceania: China and wine: Its impact on the global wine trade - Larry Lockshin (Wine Economics and Policy)
China׳s growing wine consumption is having a major effect on the global trade in wine. Growing awareness and consumption of grape-based wine in China has moved from a small number of very wealthy and often older buyers to an increasing number of younger, middle-class consumers. In this editorial, I will explore some of the effects I think this growing market is having on the wine trade and how this shapes the future research agenda for wine business related to China.